Antibacterial Activity and Cytocompatibility of Electrospun PLGA Scaffolds Surface-Modified by Pulsed DC Magnetron Co-Sputtering of Copper and Titanium - Arsalan D. Badaraev; Marat I. Lerner; Olga V. Bakina; Dmitrii V. Sidelev; Tuan-Hoang Tran; Maksim G. Krinitcyn; Anna B. Malashicheva; Elena G. Cherempey; Galina B. Slepchenko; Anna I. Kozelskaya; Sven Rutkowski; Sergei I. Tverdokhlebov (MDPI AG, 2023)
Biocompatible poly(lactide-co-glycolide) scaffolds fabricated via electrospinning are having promising properties as implants for the regeneration of fast-growing tissues, which are able to degrade in the body. The hereby-presented research work investigates the surface modification of these scaffolds in order to improve antibacterial properties of this type of scaffolds, as it can increase their application possibilities in medicine. Therefore, the scaffolds were surface-modified by means of pulsed direct current magnetron co-sputtering of copper and titanium targets in an inert atmosphere of argon. In order to obtain different amounts of copper and titanium in the resulting coatings, three different surface-modified scaffold samples were produced by changing the magnetron sputtering process parameters. The success of the antibacterial properties' improvement was tested with the methicillin-resistant bacterium Staphylococcus aureus. In addition, the resulting cell toxicity of the surface modification by copper and titanium was examined using mouse embryonic and human gingival fibroblasts. As a result, the scaffold samples surface-modified with the highest copper to titanium ratio show the best antibacterial properties and no toxicity against mouse fibroblasts, but have a toxic effect to human gingival fibroblasts. The scaffold samples with the lowest copper to titanium ratio display no antibacterial effect and toxicity. The optimal poly(lactide-co-glycolide) scaffold sample is surface-modified with a medium ratio of copper and titanium that has antibacterial properties and is non-toxic to both cell cultures.